2020
DOI: 10.3390/rs12071210
|View full text |Cite
|
Sign up to set email alerts
|

A Random Forest Modelling Procedure for a Multi-Sensor Assessment of Tree Species Diversity

Abstract: Earth observation data can provide important information for tree species diversity mapping and monitoring. The relatively recent advances in remote sensing data characteristics and processing systems elevate the potential of satellite imagery for providing accurate, timely, consistent, and robust spatially explicit estimates of tree species diversity over forest ecosystems. This study was conducted in Northern Pindos National Park, the largest terrestrial park in Greece and aimed to assess the potential of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 66 publications
2
22
0
1
Order By: Relevance
“…The medium spatial resolution of Landsat imagery can map the community of tree species; however, it cannot identify individual tree species. The Sentinel 2 was not used in any studies, but most recent studies, including Mallinis et al [106], have shown its robustness for modeling tree species diversity. The authors found that Sentinel 2 performed better than RapidEye, which has a higher spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
“…The medium spatial resolution of Landsat imagery can map the community of tree species; however, it cannot identify individual tree species. The Sentinel 2 was not used in any studies, but most recent studies, including Mallinis et al [106], have shown its robustness for modeling tree species diversity. The authors found that Sentinel 2 performed better than RapidEye, which has a higher spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple linear regression (MLR) models have been widely applied in predicting plant species diversity using environmental and spectral factors. One of the assumptions is that there is no linear relationship among explanatory variables while using MLR models (Mallinis et al 2020). Unfortunately, multicollinearity is a prevalent problem in the linear regression models solved by ordinary least square (OLS) methods.…”
Section: Methodsmentioning
confidence: 99%
“…A huge amount of observation data, generated from these monitoring networks, has improved our ability to recognize and monitor the change of PSD (Boucher et al 2020, Moudry andDevillers 2020). Focusing on site-scale surveys, traditional field-based methods can provide valuable and high-quality data at plot scale (Mallinis et al 2020). However, predicting species diversity over large areas still remains a challenge due to the difficulties of data acquisition (Mallinis et al 2020;Rocchini et al 2015), as well as the bias generated from the sampling process and strategy (Lohmus et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations